PENGENALAN FLIPPED CLASSROOM PADA BLENDED LEARNING UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SMA DI TEHORU - Ramadhani, Widya Putri; Molle, Juliana S; Sabandar, Vederico P (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2022)
The implementation of this community service aims to help school teachers adapt to technology in learning during Distance Learning activities and the preparation of Face-to-face Learning at Senior High Schools in Tehoru District, where the problems faced are related to Teacher Pedagogic Competence Improvement. The object of this activity is all high school teachers in Tehoru District. In general, the problems are: (1) The teachers' pedagogic ability is still low in delivering interesting materials for students; (2) Teachers find obstacles in adapting technology, especially in the era of online learning; (3) Not yet optimal video content or teaching materials provided by teachers to students during Distance Learning; and (4) The limited ability to make learning videos. Based on the problems faced, the Service team offers solutions, namely: (1) Introducing and identifying various platforms and applications that can be used by teachers for learning and assessment according to the subjects being taught; (2) Maximizing the use of Youtube, WhatsApp and Google Classroom applications for learning and assessment; (3) Integrating learning platforms and applications with features in Google Classroom; (4) Introduction of Flipped Classroom for online learning; (5) Assignment of making lesson plans with the flipped classroom method for online learning. The results of filling out teacher questionnaires before and after being given training were generally satisfied and understood the material presented. Thus, the teacher's pedagogic competence increases after applying Flipped Classroom in this Blended learning. This activity went smoothly and the teachers were very enthusiastic to apply these skills in teaching activities in schools during blended learning